A influência de fatores ambientais na riqueza e composição da micota liquenizada em área de brejo de altitude e caatinga - Silva, Jeanne dos Reis (2015)
Lichens are the result of an symbiotic interaction between fungus, the mycobiont, and one or more photosynthetic components, the photobionts, which can be a green algae and/or a cyanobacteria. This study aimed to compare the species richness and composition of corticolous crustose lichens in two forest types, Caatinga and Brejo de Altitude, in relation to the influence of biotic and abiotic parameters such as light, bark pH and diameter at breast height (DBH) of the host, and elevation. To collect the lichens two transects of 300 m each were delimited, one per site. Along these transects, sampling points were marked every 10 m, in a total of 30 points per site and 60 points for the whole work. For each of the points, the nearest tree was selected which had a lichen cover at the height of 0.5 m to 1.50 m from the ground on the tree trunk. The species richness and composition for each area were analyzed. Altogether, 576 samples were collected, totaling 96 species of corticolous microlichens. There was no significant difference in species richness between the two areas. With respect to the species composition, the areas were different, but with some common species between them. Comparing the species richness of corticicolous lichens with biotic and abiotic factors, only the diameter at breast height (DBH) of the selected host presented a significant relationship. Relating the composition and biotic and abiotic factors, we had elevation, DBH and vegetation types, canopy openness, influencing the species composition. Thus, the results presented in this study are intended to contribute to the ecological knowledge of lichenized fungi, and enhancing the ecological and lichenological knowledge on Caatinga and Brejo de Altitude.